Revisiones y Reflexiones. Alfabetización informativa en las Escuelas: el papel del licenciado en Bibliotecología - Simone da Rocha Weitzel; Alberto Calil Junior; Daniele Achilles (Revista Interamericana de Bibliotecología, 2015)
Taking into account the new trends in Information Literacy that a teacher requires in a classroom and a librarian in the library to guarantee the necessary integration of theoretical practical contents, the objective of this article is to present an international debate on the role of a teacher and of a librarian in secondary schools via documentary research. Thus, we highlight the importance of a bachelor of Library Science as a professional who combines necessary knowledge of Library Science and teaching to promote teaching and learning based on the development of information literacy skills and learning in schools. The issues raised shall be useful to reflect on a proposal to incorporate contents in information literacy, both in teacher training, especially in the training Bachelors of Library Science, and secondary school student training. This strategy is considered an alternative to strengthen young men and women's training to acquire the knowledge necessary to develop autonomy and students' critical sense in a scenario of data saturation.